The Effect Of Team And K3 Cooperation (Health, Safety, Work) On Performance Of Employees, CV Anugerah Panen Raya In Surabaya - Kiswah Intifadhah Akbar Rizky (NAROTAMA UNIVERSITY, Indonesia, 2019)
Quality human resources are needed in obtaining the success of the company. This study aims to determine the effect of teamwork and k3 (health, safety, work) on employee performance in Surabaya. The type of research used is quantitative research with a sample of 50 employees of the harvest harvest award who filled the questionnaire as all employees. The data analysis technique used is multiple linear regression analysis. The results showed that teamwork and k3 (health, safety, work) simultaneously had an effect on employee performance in Surabaya. As well as teamwork and k3 (health, safety, work) have a partial effect on employee performance in Surabaya. The higher the teamwork and good health, safety, work, the higher the employee's performance.